Treatment of hemimandibular hyperplasia by computer-aided design and computer-aided manufacturing cutting and drilling guides accompanied with pre-bent titanium plates. Issue 1 (January 2020) - Du, Wen; Yang, Minyue; Liu, Hanghang; Ji, Huanzhong; Xu, Chunwei; Luo, En
Abstract: Purpose: The treatment of hemimandibular hyperplasia (HH) is difficult by performing condylectomy and orthognathic surgery in one stage. This study investigated the clinical feasibility of treating HH with computer-aided design and computer-aided manufacturing (CAD/CAM) cutting and drilling guides and the pre-bent titanium plates to improve the accuracy of operation to avoid condyle reconstruction. Methods: 12 patients diagnosed with HH were included in this study from 2014 to 2018. Conservative condylectomy and bimaxillary orthognathic surgery were performed in all patients. The CAD/CAM cutting and drilling guides and the pre-bent titanium plates were used to guide surgeries. Follow-up and radiographic examinations were performed. The difference between virtually simulated and postoperative models was measured. Results: All patients got satisfactory and stable results, without complications or obvious relapse during follow-up. Occlusion relationship, temporomandibular joint function and facial symmetry were improved obviously after surgery. Comparison between simulated plans and actual postoperative outcomes showed that the surgical plans were transferred accurately. Conclusions: CAD/CAM cutting and drilling guides and the pre-bent titanium plates described in this paper can help transferring the results from computer simulation to the operating room accurately. Conservative condylectomy can be operated exactly matching bimaxillary orthognathic surgery for treating HH, avoiding condyle reconstruction.